Successful Use of Ertapenem for the Treatment of Enterobacter cloacae Complex Infection of the Central Nervous System (CNS). (5th November 2019) - Shah, Sunish; McManus, Dayna; Topal, Jeffrey E.
Abstract : A 55-year-old female with a past medical history of cocaine use and hypertension was admitted for intracranial hemorrhage requiring right decompressive craniotomy with duraplasty. Due to persistent fevers, a head CT scan obtained on day 28 of hospitalization identified a low-density subgaleal fluid collection overlying the duraplasty. Aspiration of this collection was sent for culture which grew 2+ Enterobacter cloacae complex susceptible to sulfamethoxazole-trimethoprim (SMX-TMP), gentamicin, ciprofloxacin, and ertapenem. Based on these results, the patient was transitioned from empiric vancomycin and ceftazidime to SMX-TMP and metronidazole. Despite treatment with SMX-TMP and metronidazole, aspirated subgaleal collection cultures remained positive for E. cloacae . Intrathecal gentamicin was therefore added; however, repeat subgaleal culture collections remained persistently positive. Given the persistently positive subgaleal culture collections, the patient was transitioned from SMX-TMP and metronidazole to ertapenem. After transition to ertapenem, subgaleal cultures were sterilized and the patient's infection was resolved. This report suggests ertapenem may be a viable option for central nervous system infections; however, further study is needed.